Optimalisasi Layanan Anggota Koperasi SMK Nurul Barqi Semarang melalui Digitalisasi Tata Kelola Sisa Hasil Usaha - Sakitri, Wijang; Maftukhah, Ida; Farliana, Nina (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
SMK Nurul Barqi Cooperative faces several problems, such as delayed cooperative development due to concerns about members' distrust, limited human resources, lack of management competence of administrators and supervisors, and limited knowledge and skills in reporting SHU to members. This community service aims to provide training on financial management, especially reporting SHU of cooperatives, with the hope of increasing the knowledge and competence of administrators and supervisors of SMK Nurul Barqi Cooperative in managing their cooperatives. This activity was carried out at SMK Nurul Barqi Semarang, involving 14 participants consisting of administrators and supervisors. The community service method used workshops and Focus Group Discussions (FGD), with stages of activity including initial identification, FGD for cooperative development, product design collaboration, SHU governance digitalization workshop, and program evaluation. The results of this community service were that teachers were given training on digitalizing cooperative management, correctly developing a technology-based SHU recording system, and integrating financial reporting systems more effectively and efficiently. The result was an increase in management skills for cooperative administrators. The success of this community service program is also reflected in the number of training participants that met the target, the achievement of the workshop's objectives in optimizing SHU governance through digitalization to improve participant services, coordinating materials according to plan, and the ability of participants to understand materials related to cooperative digitalization.